Knowledge, attitudes, and practices towards occupational vaccinations in a private hospital setting in Tshwane, South Africa - van Wyk-Heath, Marelize; Mapungwana, Pheyiye; Chadyiwa, Martha (Orapuh Journal, 2025)
IntroductionVaccines have prevented more morbidity and mortality over the past century than any other medical advancement. However, many healthcare workers (HCWs) in South Africa (SA) have been affected by occupational exposure to vaccine-preventable diseases (VPDs).PurposeThis study aimed to investigate the knowledge, attitudes, and practices (KAP) of selected HCWs towards occupational vaccination.MethodsAn observational, cross-sectional survey design was employed. Participants completed an online questionnaire consisting solely of close-ended questions. A non-probability voluntary response sampling method was used due to the low response rates observed in previous studies involving this population. A subset of participants representing Region 6 of Tshwane in the private sector was selected. Data were coded and analysed using the Statistical Package for Social Sciences (SPSS), version 28.ResultsA total of 149 responses were obtained. The majority of participants were female (95.7%), aged 30–49 years (63.2%), and of Black ethnicity (70.9%). Just over half held a diploma (52.1%), and most were nurses (87.2%). The HCWs demonstrated an overall knowledge level of 68.9% regarding occupational vaccinations. They also showed an above-average positive attitude (64.3%) and just over half (52.1%) reported engaging in positive practices related to occupational vaccination.ConclusionThe overall findings indicated generally positive knowledge, attitudes, and practices among these HCWs regarding occupational vaccination. A comprehensive occupational vaccination guide is recommended to better inform HCWs about VPDs and improve vaccination practices. Furthermore, the National Department of Health’s Electronic Vaccination Data System (EVDS), initially developed to track COVID-19 vaccinations, could be expanded to collect and analyse more comprehensive data on HCWs’ vaccination status, as well as morbidity and mortality related to VPDs.